ETHYL PROSPECTS REPLACEMENT FLUID COMPOSED OF ALIPHATIC ALCOHOLS AVIATION GASOLINE: THE IMPACT ON ENVIRONMENTAL CLEANLINESS - Бойченко, С. В.; Личманенко, О. Г.; Посипайко, М. А. (Science-based technologies, 2016)
In the article the advantages ethyl fluids that have caused its popularity as an anti-knock additive in gasoline and aviation part of its environmental drawbacks are that caused the ban in Ukraine. The effect of replacing ethyl fluid aliphatic alcohols on the environmental safety of aviation gasoline for traditional сhemmotology indicators: the emission products of combustion (to combustion products include: CO2 and NOx, SO2), on carcinogenicity, in toxic component composition fuel and on toxic products of incomplete combustion.